The Investigation EFL Students Reading Interest in Webtoon Application for Studying or Entertainment? - Priscillia Ika Saputri; Dzulfikri Dzulfikri (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Interest in reading is an activity carried out without coercion from others but comes from yourself. Interest in reading can grow if students have a high interest in reading. This study investigates the EFL students’ reading interest in the Webtoon Application. Its purpose is to know the students’ interest in reading Webtoon for studying or entertainment. Webtoon is a type of digital comic that originated in South Korea. Webtoon contains a collection of storytelling images published online with several genres such as drama, fantasy, comedy, horror, and a slice of life and has five languages available, they are Korean, Japanese, Thai, English, and Indonesian. The research used qualitative design as a method for collecting the data. Therefore, the instruments used to collect the data were observation, interviews, and documentation. The data were collected and analyzed by doing observations with the students outside the class. It was conducted at the English Department in the 5th semester of IAIN Madura which consisted of students who were interested in reading Webtoons. The finding showed that EFL students reading interests in Webtoon Applications were: 1) hobby, 2) story, 3) picture/visual, 4) information and 5) genre. Based on the research results, the researchers concluded that EFL students’ reading interest in Webtoon Applications is just for Entertainment not for studying to increase their English skills as Students of the English Department. Keywords: EFL Students, Reading, Reading Interest, Webtoon Application, Vocabulary